Energy–aware distributed scheduling for multimedia streaming over Internet of Things. (30th July 2013) - Cui, Jingwu; Chen, Jianxin; Zheng, Baoyu
The support for multi–user multi–source multimedia streams in Internet of Things (IoT) requires an optimal distributed scheduling scheme, ascertaining the reasonable links for transmitting each stream with QoS requirements. Moreover, since IoT is energy–sensitive, therefore, energy saving is a critical issue for IoT. In this paper, we investigate the combination of the energy saving and distributed scheduling in a united convex optimisation formulation and propose energy–aware distributed scheduling scheme based on cross–layer design. We first develop an energy–aware distortion model which describes both the distortion resulting from the coder and transmission. Then, an optimal distributed scheduling scheme is realised by adapting the transmission rate with the transmission range and minimising the overall energy consumption. Moreover, extensive simulations are provided, which demonstrate the effectiveness of our proposed energy–aware distributed scheduling in the context of IoT.